Finite element simulation of machining AISI 1045 steel using uncoated carbide tool - Mohmd Arifin, Nabila Afif (2012)
In recent years, finite element methods (FEM) have become widely used in research and industrial applications because of the advancements in computational efficiency and speed. FEM is a useful tool for the analysis of metal cutting process where this method provide better prediction of process variables whereas interaction of the tool and the chip can also be examined. Much cutting force models have been developed to predict the machining parameter. Most focus mainly on dry conditions even though coolants are widely used in practical machining. Research for modeling of minimal quantity lubricant (MQL) conditions is scarce and not really established. The use of coolants in machining makes it very difficult to determine the friction coefficient at the tool-chip interface. Hence, a better understanding of friction modeling is required in order to produce more realistic finite element models of machining process. In this study, a rigorous investigation on the role played by the implemented friction model within a 2D simulation was carried out. The simulation tool used for the purpose of this study is DEFORM2D. DEFORM 2D can simulate large deformation accompanied by elastic, plastic, thermal and friction effects. The simulation results on cutting forces and temperature were compared with experimental measurement in order to verify wether it is possible to identify the best friction model and indicate the consistency and accuracy of the results when conducting the comparison. From the result, it shows that friction models affect predicted result for both cutting force and temperature in dry and MQL conditions.